Preparação para qualidade de vida no trabalho: análise de um curso na perspectiva de servidores públicos federais - França, Luane Resende (2019)
The adoption of practices that can be called Quality of Life passes through a wide range of determinants. Some factors are known to be subjective, like emotional states; others are of objective nature, such as the work process. Nevertheless, both sets merge and produce the need for new confrontations, aiming towards a collective construction in the work spaces. The result of the research allows the course (research object) to be evaluated by the workers, to suffer interventions and/or modifications in its format, adapting it to the demands of the servers. The purpose of this study was to analyze the contributions of a training course in the DL (Distance Learning) modality about the QLW (Quality of Life at Work) for professionals of the Federal Public Service, to seek the meanings of QLW before and after the course frequency, the reciprocal influence between work and personal life, and to obtain an evaluation regarding the adopted method (DL). This is a qualitative methodology study, in which a questionnaire was applied for socioeconomic characterization and an audio-taped semi-structured interview was conducted as well as secondary sources. The research was carried out at the Federal University of Uberlândia and a sample was composed of 10 participants of both genders of the Federal Public Server's Work Quality of Life at Work Preparation Course (object of study in this research), established in 2017. The narratives obtained with the interviews were reviewed vigorously according to the content analysis in the thematic modality, which allowed the emersion of three categories namely: 1) The plurality of lived experiences that generate meanings of “QLW” bringing factors essential to the meanings of Quality of Life at Work from the perspective of the participants; 2) "I will not wait until I retire to start living": the pendular movement of the quality of life in social relations that discusses the valuation of time spent at work and how work influences the family and the health of the worker, and finally, 3) It is the distance, "but we do not distance ourselves from the course" that addresses the potentialities and challenges of the DL method. As a result, the study demonstrated that the characteristics of the work context that can be sources of well-being are: healthy environment, good socio-professional relations, a sense of usefulness that the work provides, appreciation of the time the worker spends at work, in consideration of family requirements, the need to take care of oneself and their professional fulfillment. On the contrary, among the malaise generators are inadequate work conditions, exaggerated demands for efficiency, problems with colleagues and/or managers, lack of recognition and inadequate working hours. These results allowed to observe that the factors mentioned above are elements that constitute a QLW based on the counterhegemonic approach, which is focused on the needs of the workers. The DL Method is being proven as an effective modality of education, enabling attendance, quality and access to learning. Furthermore, it can be perceived as a lower cost method that can rapidly reach a larger number of people.